Impact of the implementation of a digital tool with artificial intelligence in the financial assessment of MSMEs in Chimbote - Plácido, Juana Maribel Manrique; Garcia, Luis Alberto Torres; Aldana, Luis Miguel Mosquera; Tineo, Norma Socorro Ramirez (Edelweiss Applied Science and Technology, 2025)
This study analyzes the impact of implementing a digital tool based on artificial intelligence in the financial assessment of MSMEs in Chimbote, specifically through the design and implementation of a digital tool. A quasi-experimental design was used with two groups of MSMEs (control and experimental). The results showed that the tool significantly improves indicators such as liquidity, management, solvency, and profitability, reduces errors, and optimizes financial processes, increasing precision and efficiency in strategic decision-making. The methodology, with a quantitative approach and quasi-experimental design, included pre- and post-test surveys. This study concludes that the integration of AI in financial assessment is essential to modernize accounting practices and strengthen business competitiveness, and it recommends promoting training and the use of complementary technologies to enhance its implementation.